Microencapsulation of iron in a reversed enteric coating using spray drying technology for double fortification of salt with iodine and iron. Issue 2 (11th March 2016) - Dueik, Verónica; Diosady, Levente L.
Abstract: Prevention of iron deficiency, the most widespread nutritional disorder, can be achieved by salt double fortification; however, iron addition requires the prevention of iron‐iodine interaction. For this purpose, reversed enteric coated iron‐containing microparticles were developed in this study. Microparticles were produced using either of two coating materials: Eudragit EPO and chitosan. Coating material solutions were loaded with increasing amounts of iron and then spray dried. Maximum payloads were established and functionality/morphology of microparticles was assessed. Microparticles were added into iodized salt with different moisture contents and adhesion and stability was measured during storage. Eudragit EPO is unsuitable for iron fortification, as even low payloads prevented solid particles formation. Chitosan was an effective iron coating as good functionality/morphology was achieved with loadings up to 25%. The best particles were spherical (∼10 µm average diameter) and retained the encapsulated iron at pH 7 and released it at pH 1. Chitosan microparticles can be properly attached to the surface of coarse salt when the initial moisture content of salt is 2.4%, and iodine retention after 12 weeks storage was 90% at 25C and 70% at 45C. Chitosan is suitable for producing an iron premix for stable salt double fortified with iodine and iron. Practical Applications: Double fortification of salt with iodine and iron has been proved to be effective in reducing iron deficiency prevalence in India. Current fortification approaches use iron particles developed using an extrusion or fluidized bed agglomeration processes, to match the size and appearance of salt grains. However, in the developing world, the most consumed salt type is coarse salt. This fact imposes the need for developing iron microparticles that can be attached to the surface of coarse salt. Salt requires 2.4% moisture for good attachment. Iron microparticles must be stable in such environment. This can be achievable using reversed enteric coatings for avoiding the interaction of iodine and iron during salt preparation and storage.